Bufadienolides from the skins of Bufo melanosticus and their cytotoxic activity. (June 2019) - Meng, Lingjie; Jiang, Nian; Yu, Changyan; Li, Sanhua; Chun, Zeli; Zhu, Xinting; Song, Changwei; Xiao, Yi; Hui, Jing; Qin, Ying; Liu, Yun
Graphical abstract: Highlights: Systematically investigated the aqueous extracts of dried skins of B. melanosticus Schneider. Three new bufadienolides, together with three known analogs were isolated. In vitro assays, the new compounds showed strong cytotoxic activity. Abstract: Three new bufadienolides, (2 β, 5 β, 14 β )-2, 5, 14-trihydroxy-bufa-20, 22-dienolide (1 ), (3 α, 16 β )-3, 16-dihydroxy-bufa-14, 20, 22-trienolide (2 ) and (3 β, 5 β, 16 α )-3, 5, 16-trihydroxy-bufa-14, 20, 22-trienolide (3 ), together with three known analogs (4-6 ), were isolated from the aqueous extracts of the skins of Bufo melanosticus . Their structures were determined by spectroscopic studies, including HR-ESIMS and NMR data analyse. In the preliminary assay, all the above mentioned compounds showed cytotoxic activity against the carcinoma cell lines Bel-7402, HO-8910 and HCT-116, with IC50 values ranging from 0.01 to 24.07 μM, consistent with the practical application of toad skin and cinobufacini (Hua Chan Su).